Efficacy and Safety for the Combination of Levosalbutamol, Ambroxol and Guaifenesin for the Symptomatic Treatment of Productive Cough: Phase IV Clinical Trial - Kiran, Dr. Mayuresh Dilip; Pawaskar, Lalit Jeevan; Sheikh, Shaheen Naseem (International Journal of Innovative Research in Medical Science, 2019)
Background: Cough is one of the most common symptom that most of the Doctors faces while practising in paediatric population. Cough can be productive or unproductive. Productive cough can be treated with the combination of bronchodilator, expectorant and mucolytics. The main objective of the Phase IV clinical trial conducted was to test the efficacy and safety for the combination of Levosalbutamol (bronchodilator), Ambroxol Hydrochloride (mucolytic agent) and Guaifenesin (expectorant) for the treatment of productive cough associated with bronchospasm in conditions such as bronchitis and bronchial asthma as well as all conditions associated with tenacious mucus, wheezing and chest congestion. Methodology: The trial was conducted with 23 paediatric speciality Doctors on 325 patients out of which 149 patients were of age group 2 to 12 years and 176 were of age below 1 year. Efficacy assessment was done by analysing the cough severity score at all the visits. Safety assessment was done by analysing the adverse events experienced by the patients or observed by the investigators at all the visits. Results: At baseline, CSS was 6.624 reduced to 3.744 at day 3 and 1.049 at day 5. One point reduction in Likert type symptom scale from moderate to mild was in just 5 days. Only 12.923 % of patients experienced non-serious adverse events. Conclusion: Combination of Levosalbutamol, Ambroxol Hydrochloride and Guaifenesin was safe as well as efficacious for the treatment of productive cough.